The Effectiveness of Discovery Learning Strategy on Achievement Among Eleventh Grade Literary Students in Principles of Philosophy - Ismael Ibrahim Ahmed (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This study investigated the effectiveness of discovery learning strategy on academic achievement among eleventh-grade literary students in Principles of Philosophy. The researcher employed a quasi-experimental design with two equivalent groups consisting of 62 students purposefully selected from Shanaz Preparatory School for Girls during the 2024-2025 academic year. The sample was randomly divided into an experimental group (n=31) taught using discovery learning strategy and a control group (n=31) receiving traditional instruction. After verifying group equivalence across six variables, the researcher covered the second unit of the curriculum, comprising three chapters: Epistemology and Theory of Knowledge, Metaphysics and Reality, and Philosophy of Mind. To achieve research objectives, the researcher developed 30 detailed lesson plans for each group and constructed an achievement test consisting of 35 items in its final form, distributed across Bloom's cognitive levels (Remember, Understand, Apply, Analyze). After establishing validity (CVI=0.91) and reliability (α=0.86), data were analyzed using independent samples t-test. Results revealed statistically significant differences favoring the experimental group on the achievement test (t=5.874, p<0.001, η²=0.36). Based on these findings, the researcher proposed several recommendations and suggestions for future research.